Work Environment and Job Satisfaction on Financial Managers' Performance: The Moderating Role of Organisational Culture - Asnawir; Muh. Agung Paturungi; Wahyudi; Syahrial Maulana, (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the effect of work environment and job satisfaction on the performance of financial management employees, with organisational culture as a moderating variable, in the Regional Apparatus Organisations (OPD) of Pegunungan Bintang Regency, Papua. The study was motivated by persistently low performance among regional financial managers, as evidenced by Supreme Audit Agency findings on weak internal controls, delayed financial reporting, low job satisfaction, and a weak organisational culture. A quantitative approach was used, applying Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 on a saturated sample of 90 financial management employees across 30 OPDs, testing the direct effects of work environment and job satisfaction on performance and the moderating role of organisational culture. Results show that work environment has a positive, significant effect on performance, and job satisfaction has a positive, comparatively larger effect. Organisational culture has the strongest direct effect on performance and significantly moderates the work environment-performance relationship, although in a dampening rather than a strengthening direction; it does not significantly moderate the job satisfaction-performance relationship. These findings extend public-sector human resource management literature in underdeveloped, frontier, and outermost (3T) regions and suggest that local governments should improve working conditions, attend to job satisfaction, and build an adaptive, accountability-oriented organisational culture to strengthen regional financial governance